ANALYSIS OF THE STRATEGY USE OF TRANSLATING API MAGAZINE: EXPLORING THE NEW HUSTLE OF UBUD BALI - Rowena Timoteo Ceniza; Ni Made Diana Erfiani (LPPM Universitas Dhyana Pura, 2023)
The main purpose of this study is to identify the exact translation technique used to translate amagazine from English to Bahasa Indonesian. Api Magazine Vol.32 serves as the data source. Inthis research analysis uses a qualitative descriptive methodology to gather 68 data. And examineinformation derived from the book's content, mainly the back cover. Theory of Newmark (1988) thathas 18 methods of translation and Free Translation is one of the method that used in this study. onformal equivalence provides the basis for the data analysis. The. analysis showed that formalequivalence methods were used when translating this specific book from the source language to thetarget language.